The Spread of SARS-CoV-2 Infection Among the Medical Oncology Staff of ASST Spedali Civili of Brescia: Efficacy of Preventive Measures - Dalla Volta, Alberto; Valcamonico, Francesca; Pedersini, Rebecca; Fornaro, Carla; Tovazzi, Valeria; Monteverdi, Sara; Baggi, Alice; Consoli, Francesca; Ferrari, Vittorio Domenico; Grisanti, Salvatore; Conti, Elisabetta; Amoroso, Vito; et al. (Frontiers in Oncology, 2020)
Patients with cancer are at a higher risk of developing serious disease-related complications in case of contracting SARS-CoV-2. Oncology units should implement all possible preventive measures to reduce the risk of viral transmission by healthcare professionals (HCPs) to patients. We conducted a surveillance for SARS-CoV-2 infection among the staff members of the Medical Oncology Unit of ASST Spedali Civili in Brescia, one of the Italian areas most affected by the SARS-CoV-2 pandemic. The aim of this study was to demonstrate whether the recommended preventive measures, promptly implemented by the unit, have been effective in reducing the spread of the virus among the HCPs. Between February 24 and May 19, 2020, SARS-CoV-2 infection was detected in 10 out of 76 healthy HCPs (13%). Six of them developed a symptomatic disease, leading to home quarantine, and four remained asymptomatic. The infection was revealed when a serology test was performed on all staff members of the unit. In seven HCPs, in which it was possible to trace the person-to-person infection, the contagion occurred as a result of unprotected contacts or partially protected with surgical masks. In particular, four asymptomatic HCPs did not stop working, but a widespread outbreak in the unit was avoided. Adherence to the recommended preventive strategies, in particular, wearing of surgical masks by both the HCPs and the patients, is effective in reducing and preventing the viral spread.